NEEDS ANALYSIS OF TASK-BASED MODEL OF ARABIC NURSING SYLLABUS - Murodi, Ahmad; Emzir, Emzir; Rahmat, Aceng (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
The purpose of this study is to find the needs of task-based model syllabus for Arabic language learning in Nursing Academy at As-Syafi'yah Islamic University in Jakarta. Currently, most of the specific language syllabus does not fulfil the student needs and its content that is the language used is very general and did not really based on the needs of students. The study analyses the student needs using descriptive analysis method. While the data will be collected from document, questionnaire, and interview. Then, the data analysed will be validated by expert of qualitative technique. There are three steps of process will go through, namely data reduction, data display, and taking conclusion. The result of study shows that task-based model of Arabic nursing sylabus which is refered to Indonesia's national qualification framework is proper and decent to be used as the guidance of Arabic teaching and learning process at Nursing Academy of As-Syafi'yah Islamic University Jakarta.